Analysis Of Factors Affecting Nutritional Status Toddler Problems In Ponorogo Region - Eliya Rohmah (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2014)
Problems of nutritional status (malnutrition) in Toddlers in Ponorogo region is aproblem that needs attention, given the Toddler is the future of the nation. Thereforenecessary to identify the factors (food consumption, infectious diseases, knowledge, work)that affect nutritional status Toddler. So that could be conducive to preventing andovercoming.This research is analytic with Toddler population in the region are experiencingproblems Ponorogo Toddler nutritional status. The sample number 164 Toddler derivedfrom Health Center (Puskesmas) South region, Sukosari and Sukorejo, purposiv samplingwith sampling techniques.The results showed: (1) the majority of respondents (57.1%) have a habit ofgiving the consumption of foods that are not in accordance with the recommendation ofhealth, and the majority of respondents (64.3%) had a toddler with less nutritional status.While the test results showed statistically sig = 0.017 (<0.05) which means that there is acorrelation between the consumption of foods with Toddler Nutrition status issues, with alow level of the relationship (as indicated by a correlation coefficient 0.215). (2) Most ofthe respondents (Toddler) or 62.2% frequent infectious diseases, and the majority ofrespondents (Toddler) or 64.3% have less nutritional status. While the test results showedstatistically sig = 0.000 (<0.05) which means that there is a relationship between diseaseinfection with Toddler Nutrition status issues, the level of the relationship being (asindicated by a correlation coefficient 0.464). (3) Most of the respondents had a goodknowledge (52%), and most respondents (59.3%) had a toddler with less nutritionalstatus. While the test results showed statistically sig = 0.001 (<0.05) which means thatthere is a relationship between knowledge and Toddler Nutrition status issues, with a lowlevel of the relationship (as indicated by a correlation coefficient 0.285). (4) The majority(58.5%) of the respondents worked, and most of the respondents (59.3) had a toddler witha problem of malnutrition status. While the test results showed statistically sig = 0.320 (>0.05), which means there is no relationship between maternal work status issues ToddlerNutrition.It is recommended: (1) Mother Toddler always pay attention to food consumptionincludes the quality and quantity of food toddler every day and gain knowledge andinsight about a balanced nutritious food, although mothers work, (2) health worker:continue to provide education on nutrition Toddler, perform monitoring of foodconsumption and nutritional status of children and improve the comprehensive midwiferyservice. (3) Health Agencies: health education are expected to further streamline themonitoring of nutritional status of children. (4) Other Researchers: expected to developthe factors that affect food consumption can reduce the occurrence toddler nutritiontoddler problems.